FITOREMEDIASI TANAH TERCEMAR Pb DAN Zn DI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH PIYUNGAN, YOGYAKARTA - Kartika Eka Putri Srisena Siti Fatimah; Wawan Budianta (KURVATEK, 2021)
Piyungan waste disposal site is the largest waste disposal site in Yogyakarta and has an impact on heavy metals soil contamination, especially for lead (Pb) and zinc (Zn). This study aimed to analyze the effect of characteristics of polluted soil Pb and Zn contaminated soil in Piyungan site. The phytoremediation experiment was done in the polybags containing 2 kg contaminated soil samples and then was conducted in the greenhouse for three months and the plants were harvested each month. Plant samples were divided into roots and shoots part and the metal concentration was measured by ICP-AES after aqua regia digestion. The result of the phytoremediation experiment shows that Jatropha curcas and Amaranthus spinosus L. were detected along with the depth of the soil sampels taken, which indicated that the highest Pb and Zn contents were in the top soil layer. The soil characteristics in Piyungan landfill include pH, organic content, and mineral content of clay, which affect the effectiveness of absorption in the phytoremediation process, especially in montmorillonite content in the soil. This is confirmed and the results of the calculation of absorption efficiency and the calculation of mass balance and removal efficiency show that Jatropha curcas and Amaranthus spinosus L. have relatively low values. Keywords: Phytoremediation, soil, contamination, lead, zinc, waste.